2016
DOI: 10.1002/jor.23394
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of glenoid-sided lateralization in reverse shoulder arthroplasty

Abstract: The purpose of this study was to evaluate glenoid-sided lateralization in reverse shoulder arthroplasty (RSA), and compare bony and prosthetic lateralization. The hypothesis was that stress and displacement would increase with progressive bony lateralization, and be lower with prosthetic lateralization. A 3D finite element analysis (FEA) was performed on a commercially available RSA prosthesis. Stress and displacement were evaluated at baseline and following 5, 10, and 15 mm of bony or prosthetic lateralizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 13 publications
0
26
0
1
Order By: Relevance
“…Finite element analysis (FEA) simulations are often used for replicating the test setup per ASTM F2028-14, to determine worst case configuration for physical testing or to make comparisons among different designs or configurations. Several FEA studies have been performed to study the effect of implant designs, lateralization, inferior tilt of glenoid, and degree of joint conformity on glenoid baseplate-bone micromotion ( Hopkins et al, 2008 ; Virani et al, 2008 ; Hopkins and Hansen, 2009 ; Suárez et al, 2012 ; Chae et al, 2016 ; Denard et al, 2017 ; Elwell et al, 2017 ; Geraldes et al, 2017 ). The complexity of the FEA models has increased with time due to improvements in computing power and software technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finite element analysis (FEA) simulations are often used for replicating the test setup per ASTM F2028-14, to determine worst case configuration for physical testing or to make comparisons among different designs or configurations. Several FEA studies have been performed to study the effect of implant designs, lateralization, inferior tilt of glenoid, and degree of joint conformity on glenoid baseplate-bone micromotion ( Hopkins et al, 2008 ; Virani et al, 2008 ; Hopkins and Hansen, 2009 ; Suárez et al, 2012 ; Chae et al, 2016 ; Denard et al, 2017 ; Elwell et al, 2017 ; Geraldes et al, 2017 ). The complexity of the FEA models has increased with time due to improvements in computing power and software technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, results from FEA can be critically dependent on the modeling assumptions. In particular, one commonly used simplification in rTSA modeling studies is de-featuring of the screw threads from the screw shafts and the screw holes in the bone ( Hopkins et al, 2008 ; Virani et al, 2008 ; Hopkins and Hansen, 2009 ; Suárez et al, 2012 ; Chae et al, 2016 ; Denard et al, 2017 ; Elwell et al, 2017 ; Geraldes et al, 2017 ). The screw shafts are modeled as cylinders, virtually implanted in the cylindrical holes created in the bone.…”
Section: Introductionmentioning
confidence: 99%
“…While mechanical tests can be performed extensively to assess the stability of standard implants [10][11][12], for custom implants with a unique design for each patient, it is not practical to use mechanical testing to verify the stability. Alternatively, Finite Element (FE) analysis has been widely used to evaluate the influence of different implant configurations on the initial fixation of an implant [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Hopkins et al examined multiple standard designs with different screw angle inclination, concluding that increasing the screw inclination enhanced stability more than using longer and thicker screws [15]. Other studies explored instead the effect of the prosthesis repositioning (using different glenosphere sizes or bone grafting) and found that a lateralization of 10 mm was mechanically acceptable for osseointegration [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…23 It also increases back-side forces on the baseplate. 14 In addition, although lateralization may reduce notching, it may not be as effective as inferior overhang. 48 Clinically, lateralization may also be a trade-off.…”
mentioning
confidence: 99%